2019
DOI: 10.21061/jte.v30i2.a.2
|View full text |Cite
|
Sign up to set email alerts
|

Task Affect and Task Understanding in Engineering Problem Solving

Abstract: Within the self-regulated learning literature, motivation is considered to be an essential feature of students' self-regulatory processes. Additionally, task affect (i.e., personal objectives and task value) is thought to influence students' self-regulatory processes; insufficient task affect may lead to failures to selfregulate effectively. In a school setting, task affect is a form of motivation for completing the course tasks in order to attain course-level goals that are inherently valued. In this study, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, executing the task can confirm for the students whether or not they understood the task. Earlier studies have shown that when students work on similar types of tasks over longer periods of time, the way they understand the task becomes more accurate (Lawanto et al, 2019). In addition, through collaborating with peers, learners can improve their metacognitive knowledge of the collaborative task at hand .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, executing the task can confirm for the students whether or not they understood the task. Earlier studies have shown that when students work on similar types of tasks over longer periods of time, the way they understand the task becomes more accurate (Lawanto et al, 2019). In addition, through collaborating with peers, learners can improve their metacognitive knowledge of the collaborative task at hand .…”
Section: Discussionmentioning
confidence: 99%
“…However, the students' task understanding improved after accomplishing the problem-solving tasks. In a later study, it was found that when the same types of problem-solving tasks are given over longer periods of time, the students' perceptions of the task become more accurate (Lawanto et al, 2019). Fortunately, students' task understanding has been shown to evolve as they work in similar types of tasks over longer periods of time and collaborate with their peers (Hommes et al, 2014).…”
Section: Task Understandings As Conditions For Self-regulated Learningmentioning
confidence: 98%
“…Inadequate understanding of pre-requisite knowledge leads to weak interpretation of task and ultimately lead to errors in mathematics problem solving (e.g., [2], [13]). Similarly, in engineering problem solving, research has found that a significant difference between the instructor's and students' task interpretation of the assigned problems (e.g., [4], [5]). Student's ability to control motivation, thoughts and actions helps students accurately solve problem (e.g., [6], [7]).…”
Section: A Introduction and Brief Literature Reviewmentioning
confidence: 99%